Conditional stimulus choices affect fear learning: Comparing fear conditioning with neutral faces and shapes or angry faces. (27th April 2022) - Ney, Luke J.; Luck, Camilla C.; Waters, Allison M.; Lipp, Ottmar V.
Abstract: Past fear conditioning studies have used different types of conditional stimuli (CSs). Whether this choice affects learning outcomes in particular when neutral stimuli (e.g., neutral faces vs. shapes) are used is unclear. Data were aggregated across nine studies using an electric shock unconditional stimulus to test for differences in acquisition and extinction of electrodermal responses and self‐reported CS pleasantness when CSs were neutral faces or shapes (Experiment 1, N = 594) and when CSs were angry or neutral faces (Experiment 2, N = 157). Reliable electrodermal conditioning was observed in all stimulus conditions. We found stronger differential conditioning in electrodermal second interval responses and CS pleasantness and more pronounced extinction in CS pleasantness for neutral shape than neutral face CSs, but no differences in electrodermal first interval responses, the most frequently reported index of fear conditioning. For angry and neutral face CSs, there were no differences during acquisition, but the extinction of first and second interval electrodermal conditioning to angry faces was retarded relative to neutral faces. Acquisition of differential CS pleasantness, which was reliably observed for neutral face CSs, was absent for angry face CSs. The current results suggest that fear conditioning with a neutral face and shape CSs yields broadly similar results with differences limited to second interval electrodermal responses and CS pleasantness ratings. Using angry face CSs resulted in impaired extinction of electrodermal indices and no differential CS pleasantness ratings and should only be considered in studies designed to address questions about these specific CS materials. Abstract : Methodological choices like the nature of the conditional stimulus (CS) may affect fear learning. Here, we document in a very well powered analysis, that differences in fear conditioned to neutral face or shape CSs are limited to anticipatory electrodermal responses and self‐reported CS pleasantness but are not apparent in the more frequently reported electrodermal responses to CS onset. In contrast, differences in fear conditioned to angry and neutral face CSs emerge across indices of fear, in particular during extinction.